Digital slide and virtual microscopy based routine and telepathology evaluation of routine gastrointestinal biopsy specimens. Issue 6 (1st June 2003) - Molnar, B; Berczi, L; Diczhazy, C; Tagscherer, A; Varga, S V; Szende, B; Tulassay, Z
Abstract : Aims: To evaluate a recently developed digital slide and virtual microscope system, and to compare this method with optical microscopy on routine gastrointestinal biopsy specimens in both local and remote access modes. Methods: A fully computer controlled commercial microscope was used. The scanning program included object detection, autofocus, and image compression algorithms. The overall hard disk space for a gastric biopsy was between 30 and 50 MB and the scanning time was between 20 and 40 minutes. Haematoxylin and eosin stained routine gastric (61) and colon (42) biopsy specimens were selected, scanned, and evaluated by two specialists on an optical (OM) and virtual microscope (VM). Results: The overall concordance of VM and OM with the consensus diagnosis was 95.1% and 97%, respectively. Clinically important concordance was 96.1% and 98% for VM and OM, respectively. The two methods showed concordance in 92% of cases and clinically important concordance in 94.1% of cases. The reasons for discordance were image quality (one case), interpretation difference (three cases), and insufficient clinical information (three cases). Remote evaluation of the digital slides through the Internet has the advantages of the previously used static and dynamic telepathology methods. Conclusions: Diagnostic concordance was found between OM and VM. The digital slide and the virtual microscope can be alternative techniques in the computerisation of the histology laboratory and in teleconsultation services after further evaluation of time and storage constraints.